(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The tax is one of the elements of the general revenues of the state and contributes to covering its expenses. Taxes are imposed in most countries of the world. The tax proceeds depend on a set of factors that contribute either positively or negatively to the tax share by increasing or decreasing it. Therefore, the research aims to demonstrate the role of the tax examiner’s procedures in achieving the validity of the taxable base and its reflection on the tax proceeds, as well as reviewing the tax examiner’s procedures related to the tax return process. Examination and tax audit of the financial statements, as well as presenting the financial statements to an independent and impartial department, which is the Control and Internal Audit Department, which ensures that both parties examine and audit these data. The problem of the research was the lack of trust between the tax administration and the taxpayer The financial statements submitted by the taxpayer do not reflect the validity of the taxable base, which prompts the administration to follow the method of estimation according to the annual controls and at the same time prompts the taxpayer to adhere to the results of his accounts, which requires referring the data to a neutral party that ensures checking and auditing the accounts, which is the Control and Internal Audit Department through procedures The tax examiner, and the research is based on the hypothesis that the tax examiner’s procedures contribute to verifying the validity of the base, and this is reflected in the increase or decrease in the tax proceeds. It consists of two companies in addition to the interview, and the research was conducted in the Control and Internal Audit Department of the General Authority for Taxes. After studying and analyzing the financial statements of some taxpayers, a number of conclusions were reached, the most important of which is that the tax examiner’s procedures play an important role in verifying the validity of the base by examining revenues and disclosing what has been hidden from them, as well as examining expenses and excluding what has been inflated from them, and this will be reflected in the tax proceeds. by increase or decrease .